PERKEMBANGAN KELENTENG HOK HOO BIO (ç¦ååº) WONOSOBO TAHUN 1950 SAMPAI TAHUN 2012 - , WORO PRI ANGGANI, Eritrina Putri Ekantari, S.Hum., M.A. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
The existence of Hoo Hok Bio (ç¦å åº) temple is very meaningful for Buddhists, Taoists, and Confucians in Wonosobo, because it serves as an official place to pray which is protected by Indonesian government. Beside for worshipâs place, the temple is also functioning as a gathering center to strengthen the harmonious relationship among Tri Dharma communities in Wonosobo. This research aims at knowing the development of the temple since its inception in 1950, the history of the temple, the activities in the temple, the functions of the temple, and the meaning of symbols in Hok Hoo Bioï¼ç¦ååºï¼temple.